EXAMINING PEURATEB ANEUK TEXT AS A MODEL FOR THE RELIGIOUS CHARACTER BUILDING IN EARLY CHILDHOOD - Alwi, Said; Iqbal, Muhammad (UIN Sumatera Utara, 2022)
Abstract: The conduct of children is becoming more negative, and it is difficult for parents to identify the best educational model. The Aceh community possesses a peurateb aneuk text passed down through centuries. The text is assumed to contain character values that benefit the children. Therefore, this study examined the peurateb aneuk text as a comprehensive model of early childhood religious character building. It explains the character education model in the text and shows the conditions of the context. Furthermore, it interpreted language to obtain a model of the formation of early childhood religious character from the text. The result reported the character education model of godliness and aqidah from the peurateb aneuk text. These variables were instilled with the internalization model of tawhid sentences that parents interpret when putting children to sleep by chanting the peurateb aneuk poem. The chant became an intermediate medium for instilling character values in early childhood. Meanwhile, La ilaaha illallah is a tawhid phrase for Muslims with a high religious level used as a model in the cultivation of godliness and aqidah character in children from an early age. The peurateb aneuk activity becomes a madrasah for children to learn tawhid and aqidah.Keywords: Character Values, Peurateb Aneuk Text, Religious Education, Early Childhood